Medication Regimen Complexity and Unplanned Hospital Readmissions in Older People. (September 2014) - Wimmer, Barbara C.; Dent, Elsa; Bell, J. Simon; Wiese, Michael D.; Chapman, Ian; Johnell, Kristina; Visvanathan, Renuka
Background: Medication-related problems and adverse drug events are leading causes of preventable hospitalizations. Few previous studies have investigated the possible association between medication regimen complexity and unplanned rehospitalization.Objective: To investigate the association between discharge medication regimen complexity and unplanned rehospitalization over a 12-month period.Method: The prospective study comprised patients aged ≥70 years old consecutively admitted to a Geriatrics Evaluation and Management (GEM) unit between October 2010 and December 2011. Medication regimen complexity at discharge was calculated using the 65-item validated Medication Regimen Complexity Index (MRCI). Cox proportional-hazards regression was used to compute unadjusted and adjusted hazard ratios (HRs) with 95% CIs for factors associated with rehospitalization over a 12-month follow-up period.Result: Of 163 eligible patients, 99 patients had one or more unplanned hospital readmissions. When adjusting for age, sex, activities of daily living, depression, comorbidity, cognitive status, and discharge destination, MRCI (HR = 1.01; 95% CI = 0.81-1.26), number of discharge medications (HR = 1.01; 95% CI = 0.94-1.08), and polypharmacy (≥9 medications; HR = 1.12; 95% CI = 0.69-1.80) were not associated with rehospitalization. In patients discharged to nonhome settings, there was an association between rehospitalization and the number of discharge medications (HR = 1.12; 95% CI = 1.01-1.25) and polypharmacy (HR = 2.24; 95% CI = 1.02-4.94) but not between rehospitalization and MRCI (HR = 1.32; 95% CI = 0.98-1.78).Conclusion: Medication regimen complexity was not associated with unplanned hospital readmission in older people. However, in patients discharged to nonhome settings, the number of discharge medications and polypharmacy predicted rehospitalization. A patient's discharge destination is an important factor in unplanned medication-related readmissions.